Lumbar puncture or external ventricular drainage as initial treatment for acute hydrocephalus in aneurysmal subarachnoid hemorrhage: a 2-center cohort study - Wenz, Fabian; Tack, Reinier W. P.; Abdulazim, Amr Nabil; van der Zwan, Albert; Vergouwen, Mervyn D. I.; Etminan, Nima; Rinkel, Gabriel J. E. (Neurosurgery, 2025)
BACKGROUND AND OBJECTIVES:  - Acute hydrocephalus after aneurysmal subarachnoid hemorrhage (SAH) is typically treated by external ventricular drainage (EVD), which carries a risk of complications and long-term shunt dependency. Lumbar puncture (LP) may be an alternative. We compared the efficacy and safety of LP and EVD as initial treatment for acute hydrocephalus after SAH. - METHODS:  - We performed a 2-center cohort study comparing 2 different institutional approaches, with either LP or EVD as initial treatment. Patients with SAH treated within 72 hours for hydrocephalus, with Glasgow Coma Scale ≥7 and no contraindications for LP, were included. We calculated odds ratios with adjustment (aOR) for baseline predictors to compare the rates of permanent ventriculoperitoneal shunts (VPSs), clinical and radiological complications and unfavorable functional outcomes (Glasgow Outcome Scale 1-3 at 3 months) between the 2 strategies. - RESULTS:  - On admission, patients had comparable median Glasgow Coma Scale scores (LP group: 14, IQR = 13-14; EVD group: 14, IQR = 13-14), relative bicaudate indices (LP group: 1.2, IQR = 1.1-1.3; EVD group: 1.1, IQR = 1.0-1.3), and Hijdra scores (LP group: 21, IQR = 15-28; EVD group: 23, IQR = 12-28). In the LP group, 8 of 84 patients (10%) received a VPS, 22% had complications, and 40% had an unfavorable outcome. In the EVD group, 52 of 77 patients (68%) received a VPS (aOR = 0.04, 95% CI = 0.02-0.11), 38% had complications (aOR = 0.44, 95% CI = 0.21-0.93), and 49% had an unfavorable outcome (aOR = 0.59, 95% CI = 0.29-1.20). - CONCLUSION:  - We observed less permanent VPS implantations and less short-term complications after LP compared with EVD. LP can be considered as initial treatment for acute hydrocephalus, but future studies should elucidate the effects of both treatments on cognitive functioning. - - - - - Export